A Prospective Study of Inflammation Markers and Endometrial Cancer Risk in Postmenopausal Hormone Non-Users - Wang, Tao (2011)
BACKGROUND: It is hypothesized that inflammation may mediate the relationship between obesity and endometrial cancer risk. We examined the associations of three inflammation markers, C-reactive protein (CRP), interleukin (IL)-6, and tumor necrosis factor (TNF)-α, with risk of endometrial cancer. METHODS: A case-cohort study was nested within the Women’s Health Initiative, a cohort of postmenopausal women. Baseline plasma samples of 151 incident endometrial cancer cases and 301 subcohort subjects not using hormones were assayed. RESULTS: CRP, but not IL-6 or TNF-α, was positively associated with endometrial cancer risk after adjusting for age and BMI [hazard ratio comparing extreme quartiles (HRq(4)-q(1)) = 2.29; 95% confidence interval (CI) = 1.13–4.65; p(trend) = 0.012). After additional adjustment for estradiol and insulin, this association was attenuated (HRq(4)-q(1) = 1.70;95% CI= 0.78–3.68; p(trend) = 0.127). Obesity (BMI ≥ 30 kg/m(2)) was associated with endometrial cancer risk in an age-adjusted model. The obesity effect was reduced by 48%, 67%, and 77% when either estradiol, CRP, or insulin, respectively, was included in the model, and it became null when all three factors were adjusted for simultaneously. CONCLUSIONS: The association between inflammation, as indicated by a relatively high level of CRP, and endometrial cancer risk may partially be explained by hyperinsulinemia and elevated estradiol. Nevertheless, all three factors contribute to and mediate the link between obesity and endometrial cancer in postmenopausal women not using hormones. IMPACT: The association between obesity and endometrial cancer risk in postmenopausal women may be attributed to inflammation, insulin resistance, and elevated estrogen.